A Novel Robust Control Strategy For Grid-Connected PV Systems Based On Modified Direct Power Control - Azad, A.H.; Shateri, H.; Dragicevic, T.; Zhang, C. (2021 IEEE International Conference on Predictive Control of Electrical Drives and Power Electronics (PRECEDE), 2021)
This paper presented a distinct control strategy for a grid-connected PV system. The proposed control strategy includes a Beta algorithm for maximizing power extraction, an optimum PI controller for controlling the boost converter, and direct power control (DPC) based on modified sliding mode control (SMC) for controlling a three-phase grid-connected inverter. The proposed controller not only solves the issues of conventional DPC and SMC controllers (chattering of control input and variable frequency response), it also establishes a practical path for designing a robust controller in PV systems. On system parameter uncertainty and mismatch uncertainties, the proposed controller performs well. The proposed controller eliminates the necessity of any additional current control loops, resulting in a more straightforward system design and control process and a faster transient response.